The treasure map of boys [compact disc, unabridged] : Noel, Jackson, Finn, Hutch, Gideon--and me, Ruby Oliver - Lockhart, E. (Random House, 2009)
A Seattle sixteen-year-old juggles therapy, running a school bake sale, coping with her performance artist mother, growing distant from an old friend, and conflicting feelings about her ex-boyfriend and potential new boyfriends.